Dangerous Pursuits: Mediumship, Mind, and Music by Stephen E. Braude - Edge, Hoyt (Journal of Scientific Exploration, 2020)
Stephen Braude is the most prolific of the late 20th and early 21st century philosophers writing about parapsychogy, and his work in the philosophical aspects of parapsychology has been the most influential in this field for the past several decades. This book encompasses both philosophical issues in parapsychology, as well as studies in spontaneous and mediumistic investigations, and this collection spans the spectrum of his interests, including jazz. His title is an apt warning about the dangers to academics pursuing work in parapsychology; however, some suspicion towards those of us in the field can be mitigated if one produces excellent work in the field of one’s doctorate before tenure decisions, as Braude did. Dangerous Pursuits is composed of previously published articles or book chapters, but they are usually substantially rewritten in a way that makes these chapters accessible to a wide range of people, not only academics. Although the book is not divided into sections, the chapters are nevertheless arranged skillfully to focus, after an opening chapter on the fear of psi, a topic that Braude returns to throughout the book, on physical mediumship, then more generally on mediumship, and finally on more theoretical topics, with a coda on jazz.